2014
DOI: 10.1021/ic402795g
|View full text |Cite
|
Sign up to set email alerts
|

POP–Pincer Ruthenium Complexes: d6 Counterparts of Osmium d4 Species

Abstract: A wide range of ruthenium complexes stabilized by the POP-pincer ligand xant(P(i)Pr2)2 (9,9-dimethyl-4,5-bis(diisopropylphosphino)xanthene) were prepared starting from cis-RuCl2{κ-S-(DMSO)4} (1; DMSO = dimethyl sulfoxide). Treatment of toluene solutions of this adduct with the diphosphine under reflux leads to RuCl2{xant(P(i)Pr2)2}(κ-S-DMSO) (2), which reacts with H2 in the presence of a Brønsted base. The reaction in the presence of Et3N affords RuHCl{xant(P(i)Pr2)2}(κ-S-DMSO) (3), whereas NaH removes both ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 167 publications
0
15
0
Order By: Relevance
“…The ruthenium metal fragment Ru{xant(P i Pr 2 ) 2 } avoids the oxidation state four. As a result, the osmium d 4 -polyhydrides are d 6 -dihydrogens in the ruthenium chemistry, which require different synthetic procedures from those of osmium for their preparation [68].…”
Section: Ruthenium Versus Osmiummentioning
confidence: 99%
See 2 more Smart Citations
“…The ruthenium metal fragment Ru{xant(P i Pr 2 ) 2 } avoids the oxidation state four. As a result, the osmium d 4 -polyhydrides are d 6 -dihydrogens in the ruthenium chemistry, which require different synthetic procedures from those of osmium for their preparation [68].…”
Section: Ruthenium Versus Osmiummentioning
confidence: 99%
“…The scarce development of the pincer-osmium chemistry is probably due to the rooted belief that osmium is not useful in catalysis because it is a reductant and prefers to be coordinatively saturated and forms redox isomers with greater metal-carbon multiplicity [10-13]. However, recent findings have proved that osmium can be a promising alternative to the metals classically used in catalysis [14][15][16][17][18][19][20][21][22][23].The chemistry of the pincer-osmium complexes has been mainly focused on a few PCP derivatives reported by the groups of Gusev [24-28], Jia [29][30][31] and Milstein [32,33] and PNP complexes described by the groups of Caulton [34-37], Gusev [38-41], and Jia [42], along with some CCC [43-46], CCN [47], CNC [48,49], CNN [50-52], CNO [53], and NNN [54-59] species.We synthesized the diphosphines xant(P i Pr 2 ) 2 and dbf(P i Pr 2 ) 2 in 2010 [60], and subsequently started our research program on POP complexes of platinum group metals [3,[60][61][62][63][64][65], including osmium [60,[66][67][68][69][70][71]. In this chapter, we summarize the results obtained for this element until now.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1981, when Grigg and co‐workers first used RuH 2 (PPh 3 ) 4 as a catalyst in the alkylation of nitriles with alcohol, a lot of effort has been devoted to exploring various catalysts, including Ru, Rh, Ir, Pd, Os, Fe, and Mn. Of these, Ru complexes are the most reported, for example Gunanathan's group reported that Ru(PNP) (PNP = bis(2‐(diphenylphosphino)‐ethyl)amine) pincer complex showed good activity for α ‐alkylated reaction of arylmethyl nitriles .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] This methodology exhibits high atom economy, as water is the sole co-product. Homogeneous catalysts with precious metals such as Ru, [7][8][9][10][11] Ir, [12][13][14][15][16] Rh, 17 Os, 18 Au, 19 and Re 20 have been widely studied for the α-alkylation of ketones with alcohols. Although used in low loadings, these organometallic complexes are expensive.…”
Section: Introductionmentioning
confidence: 99%